Faithful Artificial Chromosome Propagation Using Spermatogonial Stem Cells. Issue 12 (December 2017) - Yamada, M.; Seandel, M.
Abstract : Artificial chromosomes are useful in making functional vectors for very large genes, studying chromosome physiology, and modeling chromosomal disorders. Shinohara et al . have succeeded for the first time in creating transchromosomic mice by manipulating spermatogonial stem cells (SSCs), which exhibited superior chromosomal stability compared with embryonic stem cells (ESCs).